Proceedings of the Twenty-Fifth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973402.55
|View full text |Cite
|
Sign up to set email alerts
|

Approximating matching size from random streams

Abstract: We present a streaming algorithm that makes one pass over the edges of an unweighted graph presented in random order, and produces a polylogarithmic approximation to the size of the maximum matching in the graph, while using only polylogarithmic space. Prior to this work the only approximations known were a folkloreÕ( √ n) approximation with polylogarithmic space in an n vertex graph and a constant approximation with Ω(n) space. Our work thus gives the first algorithm where both the space and approximation fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 12 publications
2
91
0
Order By: Relevance
“…Randomorder streams have been considered for problems including rank selection [33,20,28], frequency moments [3], entropy [21], submodular maximization [32], and graph matching [26,25,13]. Lower bounds that hold even under the assumption of random-order have been developed using multi-party communication complexity [9,7,8,16].…”
Section: Prior Workmentioning
confidence: 99%
“…Randomorder streams have been considered for problems including rank selection [33,20,28], frequency moments [3], entropy [21], submodular maximization [32], and graph matching [26,25,13]. Lower bounds that hold even under the assumption of random-order have been developed using multi-party communication complexity [9,7,8,16].…”
Section: Prior Workmentioning
confidence: 99%
“…Very recently it has been shown that it is sometimes possible to approximate the cost of the solution without even having enough space to load the vertex set of the graph into memory (e.g. [20,13,11]). Our work contributes to the study of streaming algorithms by providing a tight impossibility result for non-trivially approximating MAX-CUT value in o(n) space.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, very little is known about this problem in the streaming model which is one of the most fundamental models of the area of algorithms for big data. The only known result is a recent algorithm by Kapralov, Khanna, and Sudan [18], which computes an estimate within a factor of O(polylog(n)) in the randomorder streaming model using O(polylog(n)) space. In the random-order model, the input stream is assumed to be chosen uniformly at random from the set of all possible permutations of the edges.…”
Section: Introductionmentioning
confidence: 99%
“…A number of dynamic algorithms for matchings [16,29,3,26,12] have applied various partitioning techniques. The polylog(n)-approximation algorithm for random-order streams [18] employs a combination of both partitioning and exploration. Local exploration is applied by sublinear-time algorithms for the maximum matching size.…”
mentioning
confidence: 99%
See 1 more Smart Citation